Pertinence of the Sysmex XE‐5000™ parameters: rule of slide review in a context of 'normal' lymphocyte count (defined from control and mantle cell lymphoma blood specimens). Issue 5 (27th December 2012) - Chhuy, J.; Morel, D.; Goeddert, G.; Magaud, J.‐P.; Felman, P.; Baseggio, L.
Summary Introduction As most hematology cell analyzers, the different parameters of Sysmex XE‐5000™ are little informative in the qualitative analysis of lymphoid cells, and especially when the lymphocyte count is below 4 × 109/L (i.e., 'normal'). The aim of our study was to investigate whether some parameters and/or 'flags' not routinely provided by this analyzer, but reachable by operator could be reliable to define rules of slide review in absence of common qualitative and quantitative alarms particularly in case of 'normal' lymphocyte count. Methods Blood samples from 13 mantle cell lymphoma fully annotated cases, and 180 control specimens were studied with Sysmex XE‐5000™ analyzer. All cases did not present any anomalies in common quantitative and structural parameters. Results Using the method of area under the curve and ROC curve analysis, we described a novel threshold of alarm VAL_ABN LYMPH (≥40 instead of 100 defined by Sysmex), as well as a pertinent LyX threshold (≥89). The combination of these thresholds allowed defining a rule of slide review in context of 'normal' lymphocyte count. Conclusion Among the parameters provided by the Sysmex XE‐5000™ analyzer, the combination of the alarm VAL_ABN LYMPH and the LyX value, routinely available on a simple blood analysis appears particularly informative to trigger slide review in a context of 'normal' lymphocyte count with a good sensitivity (85%) to detect circulating lymphoma cells and with <1% of false positive results.